Archimedes Screw Turbines (ASTs) Performance Analysis using CFD Software Based on Variation of Blades Distance and Thread Number on The Pico Hydro Powerplant - Bambang Darmono; Hadi Pranoto (Institute for Research on Innovation and Industrial System (IRIS), 2022)
Pico hydro is a power plant that uses water as turbine propulsion that can generate electricity by a generator. This research will discuss the numerical analysis of the effect of the number of threads on the turbine blades. The analysis process uses the Computational Fluid Dynamic method and the software used in ANSYS FLUENT. In variation 1 uses 9 threaded blades, variation 2 uses 6 threads, variation 3 uses 4 threads. Based on the simulation results in variation 1 with the number of blades 9 threads, the highest torque at TSR 12 is 0.00984111 Nm, power is 0.007671419 Watt. The water pressure entering the turbine blades in variation 1 is 0.097098 Pascal and the water pressure coming out of the blades is 0.047954 Pascal, there is a total pressure drop of 0.4914 Pascal. Based on the torque and power values of the Archimedes turbine in the three variations, it is known that variation 1 has the best performance followed by the other two turbine variations.